The remaking of the Chinese character and identity in the 21st century : the Chinese face practices - Jia, Wenshan, 1961- (Civic discourse for the third millennium., 2001)
A discussion of indigenous Chinese cultural practices, such as face practices, and their role in civic discourse. It shows that Chinese character and identity are primarily functions of communication, and so these practices are important in reconstructing Chinese identity in the 21st century.